FUNCIÓN ADJETIVA (ATRIBUTO, PREDICADO NOMINAL Y PREDICATIVO) Y SU COORDINACIÓN (II) - Sánchez Martínez, Jesús (Myrtia, 2002)
Throughout this article on the adjective function, our main goal lays on the fact of the wide range and frequent morphological variability of the function. The starting point will always be the coordinative test through which two coordinated members make the same syntactic function. Therefore taking into account the above mentioned morphological variability, we are able to study in deep not only the attribute (or pure adjetive function), but also the noun predicate (both adjective and verbal functions), the acting predicative (both adjective and noun functions) and lastly the circumstance predicative (both adjective and adverbial functions). In this way, we are able to acknowledge that the adjective function is not only made by the regular first player of the function, that is the adjective, but also by the participle, the pronominal adjective, the genitive, the dative, the ablative, the prepositional group, the adjectival noun (and infinitive), the adjectival adverb and the adjective and adjectival clauses, as coordination among them stated in most cases.